The Protection of Women from Domestic Violence Act, 2005: Evaluating Legal and Social Impact in India - Pawar, Sudhir Sitaram; Vaidya, Sharvari (Journal of Neonatal Surgery, 2025)
The Protection of Women from Domestic Violence Act, 2005 (PWDVA) was enacted to address the issue of domestic violence, providing civil remedies alongside criminal provisions. This paper evaluates the Act’s legal effectiveness and its social impact over the past two decades. It examines the extent to which the Act has provided relief to victims, the challenges in its implementation, and its role in transforming societal attitudes towards domestic violence. The study also highlights judicial interpretations, case law, and statistical trends to assess the success and limitations of the legislation. Recommendations are proposed for strengthening enforcement mechanisms and ensuring better access to justice for victims. The paper underscores the need for a multi-faceted approach involving legal, social, and policy reforms to achieve the Act’s objectives